Transforming Financial Statement Recognition Through Blockchain and Cloud Accounting Integration - Yentina Siregar (Mandalika Institute, 2026)
The rapid development of digital technologies has transformed accounting practices and financial reporting systems. Among these innovations, blockchain and cloud accounting have emerged as important technologies capable of enhancing transparency, reliability, and real-time financial information processing. This study aims to examine how the integration of blockchain and cloud accounting transforms financial statement recognition and to identify research gaps within the existing literature. Using a qualitative library research approach, this study reviews academic publications published between 2017 and 2026. The analysis focuses on blockchain in accounting, accounting information systems, cloud accounting, blockchain–cloud integration, and financial statement recognition. The findings indicate that blockchain strengthens transaction verification, data integrity, transparency, and continuous assurance, while cloud accounting improves accessibility, scalability, and real-time financial data processing. The integration of these technologies supports a shift from traditional periodic reporting toward real-time financial statement recognition within digitally connected accounting environments. The review further reveals that financial statement recognition remains a relatively underexplored topic despite its fundamental role in financial reporting. The novelty of this study lies in the development of an integrated conceptual framework that synthesizes blockchain verification, accounting information system integration, and cloud accounting into a unified model for real-time financial statement recognition, enhanced transparency, and continuous auditing. This study contributes to the accounting literature by providing a comprehensive conceptual model of digital accounting transformation and offering directions for future research on technology-enabled financial reporting systems.